Knowledge Management Strategies to Improve Institutional Performance in Higher Education: A Study of Accredited Private Universities - Norawati, Suarni; Yantama, Akmal Andri; Kusuma, Chandra; Syahsudarmi, Siti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the influence of knowledge sharing and knowledge transfer on the effectiveness of policymaking, with organizational learning as a mediating variable, among leaders of private universities accredited at least “Very Good”. The study used a quantitative, explanatory survey design. Data were collected through a structured questionnaire with a five-point Likert scale from 93 structural officials of private universities and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results showed that knowledge sharing had a positive and significant effect on policymaking effectiveness, whereas knowledge transfer did not show a significant direct effect. However, both knowledge sharing and knowledge transfer were found to have a positive effect on organizational learning, which, in turn, significantly affected policy effectiveness and mediated the relationship between the knowledge variables and policy effectiveness. These findings confirm that policy effectiveness is not only determined by the availability or transfer of knowledge, but is highly dependent on the organization’s ability to manage learning collectively. This study provides theoretical contributions to the Knowledge-Based View and practical implications for strengthening learning-based governance in private universities.